Study of Business Advantages and Financial Management Models in the Anggur Merah Self-Reliant Village Program (Program Desa Mandiri Anggur Merah) in North Central Timor Regency, East Nusa Tenggara - Yohanes Made Supadi; Thomas Ola Langoday; Markus Asa (Indonesian Journal of Business Analytics, 2026)
This study investigates the business potential and micro-financial management practices within the Anggur Merah Self-Reliant Village Program, implemented in North Central Timor Regency, East Nusa Tenggara Province, Indonesia. Utilizing a mixed-method analytical framework, the research applies Location Quotient (LQ) and Shift Share analysis to identify sectoral specialization and regional competitive advantage. These quantitative assessments are further supported by an evaluation of financial management systems adopted by community-based business entities. Findings reveal that multiple sectors exhibit strong localization (LQ > 1) and warrant strategic prioritization for local economic development. These include food crop agriculture, plantations, livestock, forestry, manufacturing, construction, as well as services related to dining, entertainment, and recreation.  The analysis also identifies substantial deficiencies in micro-financial governance. This research contributes to the literature by integrating regional economic analysis with micro-financial management in a context-specific empowerment framework. The results suggest that aligning financial governance mechanisms with sectoral strengths can significantly enhance the sustainability of village enterprises. Furthermore, maintaining fundamental financial oversight across less specialized sectors remains essential. The proposed model offers a contextually appropriate and practically applicable approach to strengthening the long-term efficacy of rural economic development initiatives.